STUDI EXPERIMENTAL PENGARUH INDEX PLASTISITAS PADA TANAH KOHESIF PASCA KOMPAKSI MODIFIED PROCTOR TERHADAP HASIL UJI UNCONFINED, CBR, PERMEABILITAS DAN TAHANAN KONUS - Mukiyono, Aris
Modified Proctor Compaction test is one of the known compaction test methods, that usually performed in laboratory, to obtain soil compaction parameters, which are the optimum moisture content and the maximum dry density. In this research, the effect of plasticity index of soils is studied on the after compaction cohesive soil properties, more specifically, on the unconfined compressive strength, on the California bearing ratio, on the coefficient of permeability and on the Ducth cone penetration resistance of the compacted soils. It also gives some corralations between plasticity index with maximum dry density, optimum moisture content, and percent of clay.